A 500-dpi AC capacitive hybrid flip-chip CMOS ASIC - Vermesan, O. (IEEE Journal of solid state circuits)
A fingerprint detection technology that supports navigation, pointer, and fingerprint acquisition is described. The hybrid system consists of a silicon sensor substrate flip-chipped onto a mixed-signal ASIC. The sensor is linear and the finger is swiped over to scan the fingerprint. The navigation and pointer functions are based on the motion detection of the finger on the substrate sensor. Stroking and tapping the sensor substrate surface with the finger determines movement of the cursor and clicking-like mouse. To achieve 500 dpi fingerprint detection accuracy, separate process optimization for both the ASIC and the sensor substrate gives an alternative solution compared with all other silicon sensor approaches. The ASIC is 18 mm2 in 0.25-μm CMOS and the sensor is 105 mm2.